Synthesis and biological evaluation of some 4-aminoquinoline derivatives as potential antitubercular agents - Shankar Alegaon; Kamlesh Kashniyal; Sanket Kuncolienkar; Rohini Kavalapure; Preeti Salve; Mahesh Palled; Shailendra Suryawanshi; Sunil Jalalpure (SpringerOpen, 2020)
Abstract Background Based on bioisosteric similarities with thiacetazone, a series of 7-chloro-4-aminoquinoline derivatives have been designed and synthesized. The target compounds were elucidated by NMR, mass, and FTIR spectral data. All synthesized compounds were evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Rv (MTB), and human dermal fibroblast cell lines were used to assess toxicity of selected ligands. Results All of the designed compounds showed inhibition of MTB with MIC of 1.56-50 μM. Among the tested compounds, 7c and 7g proved to be most potent MTB inhibitors (MIC = 1.56 μM). Conclusions The outcome of present study suggests that most of the synthesized compounds are sensitive to Mycobacterium tuberculosis and showed acceptable range for molecular parameters. Thus, 7-chloro-4-aminoquinolines could be a useful lead for the development of new MTB inhibitory agents.